Descriptive Qualitative Analysis: Implementation of the Independent Curriculum at SMKN 1 Kedawung - Rindi Septi Ani; Suklani Suklani; Dewi Cahyani (MASI Mandiri Edukasi, 2025)
This study describes the implementation of the Merdeka Curriculum at SMKN 1 Kedawung and examines the role of teachers in its execution. The Merdeka curriculum emphasises flexibility, independence of thought, and character development of learners. Teachers have a central role as designers, implementers, and evaluators of learning in this curriculum. This qualitative research uses a literature review method and in-depth interviews with Vice Principals, senior teachers, and curriculum experts at SMKN 1 Kedawung. The results showed that although teachers have understood the concept of the Independent curriculum that has been running for almost two years, there are still obstacles in analyzing learning outcomes (CP), formulating learning objectives (TP), preparing the flow of learning objectives (ATP) and teaching modules, as well as making diagnostic assessments and learning evaluations. To overcome these obstacles, teachers implement strategies such as discussions with the MGMP team or peers and participating in online and offline training. Applying various learning models and methods, such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and inquiry, is emphasised to train students ' cognitive and psychomotor abilities and develop character. Evaluation of learning focuses on cognitive aspects, but also the character of learners through P5 (project for strengthening Pancasila student profile). Training and professional development are very influential in improving teachers' ability, as evidenced by 80% of teachers at SMK 1 Kedawung who have implemented the Independent curriculum well after attending various trainings.